Plan de marketing para los productos de la cooperativa agropecuaria Chone Ltda. - García Loor, Zobeida Elizabeth (2018)
The objective of the research was to carry out a marketing plan for the products of Agropecuaria Chone LTDA. Cooperative, which contributes to improve the commercialization of the products "La Ganadera", synthesizing phase I an interview was applied to the financial manager to know details about the current situation for what the company is going through, in the same way a market study was carried out in the Chone Canton center, through surveys aimed at a sample of the population that corresponded to 270 inhabitants, in order to know what the customer really wants, based on this commercial strategies were established to ensure the positioning of dairy products in the minds of consumers. In phase II, the analysis of the real market situation was carried out through the competitive matrix which showed that the company TONY represented a greater impact with 3.30%, putting itself ahead as the competition, in addition strategies were developed according to the SWOT through a combined matrix to use the 5W + 1H matrix and execute the action plans to achieve the established goals. With respect to phase III, the respective retail distribution channel was raised, therefore advertising policies and a promotion program were created. Finally, the proposal of the marketing plan was presented through a socialization to the manager of Agropecuaria Chone LTDA. Cooperative.